Solidification of Suspended Colloids at Nonplanar Interfaces. Issue 1 (July 2016) - Xu, Zhanping; Yu, Hongfeng; Yan, Jia; Tan, Li
Summary: Freeze‐drying has been widely used to deliver wide varieties of porous structures because of its processing ease and environment‐friendly nature. However, freezing of colloidal suspensions is also complex that depends on interplay of multiple parameters including the rate of processing, the magnitude of temperature gradient, and the portion of each component in the liquid mixture. While these parameters are relatively easy to measure and control, the mutual interaction between the growing solid‐liquid interface and the solute content in the suspension is much harder to evaluate. We present a two‐dimensional numerical model to simulate this latter scenario in a unidirectional freezing process, with a focus of colloidal particle motions at self‐evolving nonplanar solid‐liquid interface. This growing interface is determined by a real‐time thermal and constitutional supercooling in the liquid medium. We found colloidal particles can be rejected by the interface if the repelling from the interface is strong and freezing speed is low. Microscale liquid medium among colloidal particle gaps can freeze when particles are highly packed between frozen solid tips, with small pores easily frozen than larger ones. Noting all these findings are revealed by coupling our simulation with a visualization module though high performance GPU devices.